2021
DOI: 10.1038/s41598-021-95540-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of structural specificity of ZnO particles in preserving functionality of proteins in their corona

Abstract: Reconfiguration of protein conformation in a micro and nano particle (MNP) protein corona due to interaction is an often-overlooked aspect in drug design and nano-medicine. Mostly, MNP-Protein corona studies focus on the toxicity of nano particles (NPs) in a biological environment to analyze biocompatibility. However, preserving functional specificity of proteins in an NP corona becomes critical for effective translation of nano-medicine. This paper investigates the non-classical interaction between insulin an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Hence, the interactions between the ZnO NPs and BSA are likely to be reversible under certain environments. On the other hand, Singh et al demonstrated that the morphology (tetrapodal or spherical shape) of ZnO can be a critical factor preserving the functionality of proteins in the ZnO–protein corona [ 48 ]. Giannousi et al also showed that ZnO nanoflowers with sharp edges exhibited a higher amyloid degradation rate in the BSA and human insulin model proteins than ZnO NPs [ 49 ], which requires further extended investigation on a wide range of bio-matrices and NP types.…”
Section: Interactions Between Zno Nps and Bio- Or Food-matricesmentioning
confidence: 99%
“…Hence, the interactions between the ZnO NPs and BSA are likely to be reversible under certain environments. On the other hand, Singh et al demonstrated that the morphology (tetrapodal or spherical shape) of ZnO can be a critical factor preserving the functionality of proteins in the ZnO–protein corona [ 48 ]. Giannousi et al also showed that ZnO nanoflowers with sharp edges exhibited a higher amyloid degradation rate in the BSA and human insulin model proteins than ZnO NPs [ 49 ], which requires further extended investigation on a wide range of bio-matrices and NP types.…”
Section: Interactions Between Zno Nps and Bio- Or Food-matricesmentioning
confidence: 99%
“…[31,32] Although the interaction between proteins such as BSA and ZnO nanoparticles (ZnO NPs) are likely to be reversible, preserving the bio-functionality of adsorbed proteins is important for their actual and potential biomedical applications. [33][34][35][36][37][38][39] Therefore, to improve the effectiveness, efficiency and biocompatibility of zinc oxide nanoparticles, the preparation of ZnO-based nanocomposites has received considerable attention by researchers. In this study, bovine serum albumin was used as a protein model which has 75.6 % sequence homology with human serum albumin.…”
Section: Introductionmentioning
confidence: 99%